Structural insights into Plasmodium PPIases - Rajan, Sreekanth; Yoon, Ho Sup (Frontiers in Cellular and Infection Microbiology, 2022)
Malaria is one of the most prevalent infectious diseases posing a serious challenge over the years, mainly owing to the emergence of drug-resistant strains, sparking a need to explore and identify novel protein targets. It is a well-known practice to adopt a chemo-genomics approach towards identifying novel targets for known drugs, which can unravel a novel mechanism of action to aid in better drug targeting proficiency. Immunosuppressive drugs cyclosporin A, FK506 and rapamycin, were demonstrated to inhibit the growth of the malarial parasite, Plasmodium falciparum. Peptidyl prolyl cis/trans isomerases (PPIases), comprising cylcophilins and FK506-binding proteins (FKBPs), the specific target of these drugs, were identified in the Plasmodium parasite and proposed as an antimalarial drug target. We previously attempted to decipher the structure of these proteins and target them with non-immunosuppressive drugs, predominantly on FKBP35. This review summarizes the structural insights on Plasmodium PPIases, their inhibitor complexes and perspectives on drug discovery.